Monasteries and churches of Romania - Vaetisi, Adela (Noi media print, 2008)
Despre autor: Monahia Atanasia (dr. Adela Vaetisi), este muzeograf la Manastirea Stavropoleos din Bucuresti, doctor in istoria artei a Universitatii Nationale de Arte Bucuresti, autor a numeroase studii si articole aparute in reviste de specialitate, a sustinut cursuri de istoria si teoria artei la Universitatea Nationala de Arte si la Facultatea de Teologie Ortodoxa din Bucuresti. "In the last 15 years not only pilgrims, more and more of them youths catechized in schools, but also ordinary visitors go to monasteries and pray at the miraculous icons or the remains of saints. Some of them kneel to be blessed and to receive spiritual guidance from great clergy. At Nicula they can meet the learned archbishop of Cluj, Bartolomeu Anania who made the latest translation of the Holy Bible, and is widely knowledgeable in biblical science. At Sambata there is Father Teofil who administers advice and urges courage, in the Apuseni Mountains Father Rafail Noica may be found, who conveys spiritual warmth, and at Prislop, near the tomb of Father Arsenie Boca, or can meet with several men of the cloth. Their quests and dedication include the past and present, and they are the hope of the Church, which calls all, lower and higher orders of priests, monks and lay men alike, to be in the service of the poor, of the hungry, naked and sick, and also of those who are melancholy, lonely, despondent and faithless, steeled by the example of the Mother of the Lord, an image of immaculate meekness and love.